2003
DOI: 10.1359/jbmr.2003.18.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Marrow Cell Transplantation for Infantile Hypophosphatasia

Abstract: An 8-month-old girl who seemed certain to die from the infantile form of hypophosphatasia, an inborn error of metabolism characterized by deficient activity of the tissue-nonspecific isoenzyme of alkaline phosphatase (TNSALP), underwent the first trial of bone marrow cell transplantation for this heritable type of rickets. After cytoreduction, she was given T-cell-depleted, haplo-identical marrow from her healthy sister. Chimerism in peripheral blood and bone marrow became 100% donor. Three months later, she w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
95
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 71 publications
(120 reference statements)
2
95
0
4
Order By: Relevance
“…In our pilot study, we demonstrated that marrow osteoprogenitors can engraft in bone giving rise to donor-derived osteoblasts, modify the microscopic structure of the bone, and promote clinical benefits for children with OI, suggesting a contribution to osteogenesis [13,14]. Subsequent to our initial report, other investigators demonstrated that hypophosphatasia, another genetic disorder of bone, may also be treated with BMT [15,16], independently validating our original findings.…”
Section: Introductionsupporting
confidence: 77%
“…In our pilot study, we demonstrated that marrow osteoprogenitors can engraft in bone giving rise to donor-derived osteoblasts, modify the microscopic structure of the bone, and promote clinical benefits for children with OI, suggesting a contribution to osteogenesis [13,14]. Subsequent to our initial report, other investigators demonstrated that hypophosphatasia, another genetic disorder of bone, may also be treated with BMT [15,16], independently validating our original findings.…”
Section: Introductionsupporting
confidence: 77%
“…11,12 Bone marrow transplantation has been reported to treat several patients with hypophosphatasia. 13 However, a method must be developed that improves the survival of donor mesenchymal cells in patients. Likewise, other congenital enzyme defect disorders, such as Hurler or Hunter disease, recombinant enzyme replacement therapy is being attempted in hypophosphatasia.…”
mentioning
confidence: 99%
“…Two unrelated patients with worsening infantile HPP received marrow cell transplantations and survived a likely lethal outcome (Cahill et al 2007;Whyte et al 2003). Now, enzyme replacement therapy for severe HPP using human recombinant bone-targeted alkaline phosphatase provides promise for improved outcome (Whyte et al 2012).…”
Section: Discussionmentioning
confidence: 99%